Anti-c-Met monoclonal antibody ABT-700 breaks oncogene addiction in tumors with MET amplification. Issue 1 (December 2016) - Wang, Jieyi; Goetsch, Liliane; Tucker, Lora; Zhang, Qian; Gonzalez, Alexandra; Vaidya, Kedar; Oleksijew, Anatol; Boghaert, Erwin; Song, Minghao; Sokolova, Irina; Pestova, Ekaterina; Anderson, Mark; et al.
Abstract Background c-Met is the receptor tyrosine kinase for hepatocyte growth factor (HGF) encoded by theMET proto-oncogene. Aberrant activation of c-Met resulting fromMET amplification and c-Met overexpression is associated with poor clinical outcome in multiple malignancies underscoring the importance of c-Met signaling in cancer progression. Several c-Met inhibitors have advanced to the clinic; however, the development of inhibitory c-Met-directed therapeutic antibodies has been hampered by inherent agonistic activity. Method We generated and tested a bivalent anti-c-Met monoclonal antibody ABT-700 in vitro for binding potency and antagonistic activity and in vivo for antitumor efficacy in human tumor xenografts. Human cancer cell lines and gastric cancer tissue microarrays were examined for MET amplification by fluorescence in situ hybridization (FISH). Results ABT-700 exhibits a distinctive ability to block both HGF-independent constitutive c-Met signaling and HGF-dependent activation of c-Met. Cancer cells addicted to the constitutively activated c-Met signaling driven byMET amplification undergo apoptosis upon exposure to ABT-700. ABT-700 induces tumor regression and tumor growth delay in preclinical tumor models of gastric and lung cancers harboring amplifiedMET . ABT-700 in combination with chemotherapeutics also shows additive antitumor effect. Amplification ofMET in human cancer tissues can be identified by FISH. Conclusions The preclinical attributes of ABT-700 in blocking c-Met signaling, inducing apoptosis and suppressing tumor growth in cancers with amplifiedMET provide rationale for examining its potential clinical utility for the treatment of cancers harboringMET amplification.